2005
DOI: 10.1126/science.1105654
|View full text |Cite
|
Sign up to set email alerts
|

An Acylation Cycle Regulates Localization and Activity of Palmitoylated Ras Isoforms

Abstract: We show that the specific subcellular distribution of H- and Nras guanosine triphosphate-binding proteins is generated by a constitutive de/reacylation cycle that operates on palmitoylated proteins, driving their rapid exchange between the plasma membrane (PM) and the Golgi apparatus. Depalmitoylation redistributes farnesylated Ras in all membranes, followed by repalmitoylation and trapping of Ras at the Golgi, from where it is redirected to the PM via the secretory pathway. This continuous cycle prevents Ras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
729
2
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 787 publications
(817 citation statements)
references
References 38 publications
52
729
2
16
Order By: Relevance
“…Inhibition of the palmitoylation/de-palmitoylation cycle prevented accumulation and activation of H-Ras on the Golgi [64]. In this model Ras activation stimulates depalmitoylation and traffic to the Golgi where a new and distinct pool of effectors may be subsequently activated.…”
Section: Compartmentalised Ras Signallingmentioning
confidence: 91%
See 1 more Smart Citation
“…Inhibition of the palmitoylation/de-palmitoylation cycle prevented accumulation and activation of H-Ras on the Golgi [64]. In this model Ras activation stimulates depalmitoylation and traffic to the Golgi where a new and distinct pool of effectors may be subsequently activated.…”
Section: Compartmentalised Ras Signallingmentioning
confidence: 91%
“…Several advanced fluorescence based approaches [89]. Some studies have revealed endomembrane Ras activation in addition to the cell surface pool [64,[90][91][92][93], whilst others only detect plasma membranelocalised Ras activation [94][95][96]. One criticism of the evidence for endomembranous Ras activation is that it is normally seen only with over-expression of Ras.…”
Section: Compartmentalised Ras Signallingmentioning
confidence: 99%
“…2). [25,26] Non-palmitoylated K-Ras4B also traffics back and forth from the PM, although by other mechanisms: phosphorylation of K-Ras4B by PKC promotes its release from the PM and its transfer to mitochondria. [27] Calmodulin binding to K-Ras4B also dislodges it from the PM, facilitating its translocation to the GC and to early endosomes.…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
“…These isoforms of Ras diVer mainly in their C-terminal membrane anchors that determine cellular localization and micro-localization within membranes (Rocks et al 2006). For instance, within the whole cell an acylation cycle dynamically partitions H-Ras between the plasma membrane and the Golgi (Rocks et al 2005). On the other hand K-Ras is not subject to such an acylation cycle but its association with the plasma membrane is regulated via phosphorylation (Bivona et al 2006).…”
Section: Signaling Via Protein Clusters In the Plasma Membranementioning
confidence: 99%